Synthetic Applications and Methodological Developments of Donor–Acceptor Cyclopropanes and Related Compounds - O’Connor, Nicholas R. (Isr J Chem, 2016)
Donor–acceptor cyclopropanes are convenient precursors to reactive and versatile 1,3-dipoles, and have found application in the synthesis of a variety of carbo- and heterocyclic scaffolds. This perspective review details our laboratory’s use of donor–acceptor cyclopropanes as intermediates toward the total synthesis of various natural products. We also discuss our work in the development of novel cycloadditions and rearrangements of donor–acceptor cyclopropanes and aziridines, as well as an example of an aryne insertion proceeding via fragmentation of a transient donor–acceptor cyclobutane.